Telemedicine implementation and use in community health centers during COVID-19: Clinic personnel and patient perspectives - Denise D. Payán; Jennifer L. Frehn; Lorena Garcia; Aaron A. Tierney; Hector P. Rodriguez (Elsevier, 2022)
In March 2020, federal and state telehealth policy changes catalyzed telemedicine adoption and use in community health centers. There is a dearth of evidence on telemedicine implementation and use in these safety net settings and a lack of information reflecting the perspectives of patients with limited English proficiency. We conducted in-depth interviews with clinic personnel and patients during the pandemic in two federally qualified health centers that primarily serve Chinese and Latino immigrants. Twenty-four interviews (clinic personnel ​= ​15; patients who primarily speak a language other than English ​= ​9) were completed remotely between December 2020 and April 2021. Interview scripts included questions about their telemedicine experiences, technology, resources and needs, barriers, facilitators, language access, and continued use, with a brief socio-demographic survey. Data analyses involved a primarily deductive approach and thematic analysis of transcript content. Both FQHCs adopted telemedicine in a few weeks and transitioned primarily to video and audio-only visits within two months. Findings reveal third-party language interpretation services were challenging to integrate into telemedicine video visits. Bilingual personnel who provided language concordant care were seen as essential for efficient and high-quality patient telemedicine experiences. Audio-only visits were of particular benefit to reach patients of older age, with limited English proficiency, and with limited digital literacy. Continued use of telemedicine is contingent on reimbursement policy decisions and interventions to increase patient digital literacy and technological resources. Results highlight the importance of reimbursing audio-only visits post-pandemic and investing in efforts to improve the quality of language services in telemedicine encounters.